A Contribution to the Ecology of Casuarina equisetifolia in India - Puri, G. S. (Indian Forester, 1958)
In I950, some observations on the ecology of Casuarina plantations at Sriharikota Agaram, Kulithalai, and Tiruvellum were made along with Central Sriviculturist and the Forest Mycologist. The study involved the evaluation of climatic and soil features of Casuarina plantations and natural vegetation in the areas. The data tend to show that in the Kulithallai plantations, were the growth of Casuarina was the best, the soils were very fertile, with the highest amount of exchangeable Ca, high pH values, above 7.0, high organic matter and medium nitrogen. In the Ravannapachattaram plantations with poorest growth, the soils were less fertile with the lowest exchangeable Ca, lowest organic matter, low nitrogen content and medium pH (near neutral point). The water table in the former plantations was generally higher. The growth of the species seem to be influenced by soil fertility, especially the high exchanges ble Ca and moderate N content. Further evidence for tbese physiological requirements of this species was got by foliar analysis of Casuarina and 38 indigenous species that are cleared to rai.e plantations. The results of practical importance from this study are that on poorer soils Some broad leaved species should be introduced in plantations to improve the Ca status of the soil and provide mixed humus which is richer in nitrogen and has a higher water retaining capacity. On fertile soils of the Kulithalai plantations which show good growth, but plants die at places of unfavourable soil morphology as shown by Gupta or fungus as shown by Bakshi, the raising of broad-leaved species in unsuitable sites is one of the practical solutions of getting the best yield from the soil. From the management point of view it would probably be desirable to practise "Crop rotation" rather than "Crop mixture" as suggested by Dr. Kadambi.